Understanding the Genetic Basis of Type 2 Diabetes: Implications for Precision Medicine and Novel Therapeutic Approaches - Gul, Hassam; Joya, Farhat; Zafar, Ahmar; Sikander, Suleman; Akhlaq, Hamna (Indus Journal of Bioscience Research, 2025)
This research tries to quantify awareness, integration, and uptake of genetic ideas in Type 2 Diabetes (T2D) management by Punjab general practitioners (GPs). The research used a quantitative research design, whereby a self-report questionnaire was used to collect data from 110 GPs via snowball sampling. This research explores three main aims: (1) to measure the awareness of general practitioners with regard to the genetic cause of T2D, (2) to measure the extent to which genetic considerations are incorporated into T2D management, and (3) to determine predictors of the uptake of genetic information in T2D management. Descriptive statistics, Chi-square tests, and t-tests were employed for statistical analyses. Findings reveal a level of mixed awareness among GPs where 18.18% very familiar, 45.45% somewhat familiar, and 36.36% not familiar with genetic concepts of T2D. Significant gap was discovered in applying genetic factors in clinical practice where most GPs (54.55%) rarely apply genetics in managing T2D. Despite positive attitude scores for the uptake of genetic knowledge (54.55% agreeing or strongly agreeing), an extreme level of resistance to the incorporation of genetic knowledge into practice was observed. Chi-square analysis revealed that a significant association between knowledge of genetic terms and how often T2D management is thought about in relation to genetic factors existed. In addition, t-tests revealed that the difference between agreeing to use genetic knowledge and disagreeing was significant. The research emphasizes the importance of enhanced genetic education and support systems, such as genetic counselors, to assist GPs in applying genetic knowledge to practice. Future implications suggest that greater genetic literacy among health professionals and the availability of genetic testing can facilitate more personalized and effective management of T2D.